2014
DOI: 10.1002/ccd.25393
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term clinical experience with amplatzer ductal occluder II for closure of the persistent arterial duct in children

Abstract: The ADO II is effective for occlusion of PDA with variable anatomy from either arterial or venous approaches with a low profile delivery system. Stable occluder position is highly dependent on accurate device sizing, good quality imaging to visualize device configuration after deployment and operator experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 19 publications
1
18
0
Order By: Relevance
“…The efficacy and safety profiles of percutaneous patent ductus arteriosus (PDA) closure are well‐documented in older infants, children, and adults . Evidence in smaller infants, however, is limited to a few small studies with variable outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…The efficacy and safety profiles of percutaneous patent ductus arteriosus (PDA) closure are well‐documented in older infants, children, and adults . Evidence in smaller infants, however, is limited to a few small studies with variable outcomes .…”
Section: Introductionmentioning
confidence: 99%
“…Complete occlusion on echocardiography was found in 84.6% of cases immediately after the procedure and 100% at the time of discharge. The most frequent complications associated with percutaneous closure of PDA include device embolization, protrusion of the retention disk of the device into the aorta producing aortic obstruction, or obstruction of a branch pulmonary artery by the device . In the present study, no patients were found to have these complications during follow‐up.…”
Section: Discussionmentioning
confidence: 51%
“…However, to avoid completely the use of fluoroscopy, the technique of device placement itself must be as safe as possible under echocardiographic guidance. Studies of percutaneous PDA occlusion with ADO II occluder under fluoroscopy guidance indicated excellent results with occlusion rate of 96–100% and a low incidence of complications . In the present study, percutaneous PDA occlusion under TTE guidance was successfully performed in 62 patients (62/63, 98%).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…[29] ADO II device protrusion into the left pulmonary artery or the descending aorta is a possible complication of the procedure, although several studies have described the safety and efficacy of the device. [29303132333435]…”
Section: Discussionmentioning
confidence: 99%